THE FEED DIGESTIBILITY OF KAMPUNG CHICKEN (Gallus domesticus) GIVEN FERMENTED PAPAYA LEAVES (Carica papaya L.) - I G. S., Parayana; Puger, A.W.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2021)
This study aimed to determine Feed Digestibility of  Kampung Chicken (Gallus domesticus) Given Fermented Papaya Leaves (Carica papaya L.). This research was conducted at the Research Station of the Faculty of Animal Husbandry, Udayana University, Sesetan, Denpasar, Bali. Nutrients analysis were conducted at Nutrition Laboratory of the Faculty of Animal Husbandry, Udayana University. The experimental design used was a completely randomized design (CRD) consisting of 4 treatments, namely; treatment A as control (ration without additional fermented papaya leaves), treatment B (ration was given 10% fermented papaya leaves), treatment C (ration was given 15% fermented papaya leaves), and treatment D (ration was given 20% fermented papaya leaves). Each treatment had 4 replications and each replication used 3 kampung chickens aged 10 weeks. The variables observed were digestibility of dry matter, organic matter, crude protein, and crude fiber. Data were analyzed using variance. The results showed that the feed digestibility of kampung chicken given fermented papaya leaves up to 20% had no significant effect (P>0.05) on all observed variables. It can be concluded that the chicken  given fermented papaya leaves up to 20% give same effect on the feed digestibility  of kampung chickens aged 10 weeks.   Key words: fermented papaya leaves, feed digestibility, kampung chicken .